The little data book - World Bank. (Washington, D.C. : World Bank, 2000)
This is a pocket edition of the World Development Indicators intended as a quick reference for users of the World Development Indicators databse, book, and CD-ROM. It covers more than 1,000 indicators and spans more than 50 years.
Latest edition consulted: 2011.
oif 14/05/14
Reference
Keywords: Economic development; Economic history; Social indicators